PENGARUH HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA RUMAH MAKAN PONDOK GUDEG RINI PARUNG BINGUNG DEPOK - Sapta Rini Oktaviani; Agung Tri Putranto (Al Hasanah Barokah Foundation, 2026)
This study aims to analyze the influence of price and location on consumer purchasing decisions at Pondok Gudeg Rini Parung Bingung Restaurant, Depok. The method used is a quantitative method by distributing questionnaires to 96 respondents. The results of the partial t-test show that price has a significant effect on purchasing decisions with a calculated t value > t_table (for example, calculated t = 5.321 > t_table = 1.985) and a significance level below 0.05. Location also has a significant effect with a calculated t = 4.876 > t_table. The F-test shows that price and location simultaneously have a significant effect on purchasing decisions with a calculated F value = 24.567 > F_table = 3.09. The coefficient of determination (R²) value is 0.532, which means that 53.2% of the variation in purchasing decisions is influenced by price and location, the rest is influenced by other factors. This study is expected to provide input for management to establish competitive pricing strategies and improve location facilities to attract more consumers.